Role of socioeconomic factors in developing mycetoma: Results from a household survey in Sennar State, Sudan. - Natalia Hounsome; Rowa Hassan; Sahar Mubarak Bakhiet; Sahar Mubarak Bakhiet; Kebede Deribe; Stephen Bremner; Ahmed Hassan Fahal; Melanie J Newport (PLoS Neglected Tropical Diseases)
Background Mycetoma is a chronic, progressively destructive disease of subcutaneous tissues and bones caused by certain species of bacteria or fungi. We conducted a cross-sectional community-based study alongside mapping of mycetoma in five administrative units with high mycetoma endemicity in the Eastern Sennar Locality, Sennar State, Sudan. Methods A household survey was administered which included questions about the household members, household characteristics, economic activity and history of mycetoma. A clinical examination was conducted on all members of the household. If mycetoma was suspected, an individual questionnaire was completed collecting demographic, clinical and epidemiological data as well as information on the use of health care and associated costs. Geographical coordinates and photos of the lesions were taken, and the affected persons were referred to the medical centre for confirmation of the diagnosis and treatment. We compared the characteristics of households with confirmed cases of mycetoma with those without confirmed cases, and individuals with confirmed mycetoma with those in whom mycetoma was not confirmed. Results In total 7,798 households in 60 villages were surveyed; 515 suspected cases were identified and 359 cases of mycetoma were confirmed. Approximately 15% of households with mycetoma had more than one household member affected by this disease. Households with mycetoma were worse off with respect to water supply, toilet facilities, electricity and electrical appliances compared to the survey households. Only 23% of study participants with mycetoma had sought professional help. Of these, 77% of patients travelled an average of six hours to visit a medical facility. More than half of patients had to pay towards their treatment. The estimated average cost of treatment was 26,957 Sudanese pounds per year (566 US dollars, exchange rate 2018). Conclusions Results of this survey suggest that agricultural practices and reduced access to sanitation and clean water can be risk factors in developing mycetoma. Poor access to health care and substantial financial costs were barriers to seeking treatment for mycetoma.